(untitled) (Филолошки студии, 2019)
This text is concerned with the opposing in the meaning of the word «komshija» trough a socially cultural context, in the past and nowadays. The word «komshija» is of Turkish origin, accepted by the languages of the balcanian nations that had been several centuries under Turkish domination. In the sense of communication, the relations between the neighbours had always been diverse, contradictory, but nevertheless close. As such, for a long time they stood to be the inspiration of many anecdotes, different forms of folklore and later of literature as well. Today, on the contrary, in this urban balcanian life, transitional and alienated as it is, the term «komshija» seems to be loosing its intimate essence, as it is slowly being replaced by another type of intimate human relations, strongly influenced by the Internet. Apparently, the prior «komshija» is meant to rest in peace in the photo album of past times.